2018
DOI: 10.1177/1756285617753365
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of cladribine tablets on MRI activity outcomes in patients with relapsing–remitting multiple sclerosis: the CLARITY Extension study

Abstract: BackgroundThe CLARITY and CLARITY Extension studies demonstrated that treatment of relapsing–remitting multiple sclerosis (RRMS) with cladribine tablets (CT) results in significant clinical improvements, compared with placebo. This paper presents the key magnetic resonance imaging (MRI) findings from the CLARITY Extension study.MethodsPatients who received a cumulative dose of either CT 3.5 or 5.25 mg/kg in CLARITY were rerandomized to either placebo or CT 3.5 mg/kg in CLARITY Extension. Patients from the arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…the majority of patients for at least a further 2 years, without further treatment and despite recovery of median total lymphocyte counts to within the normal range. There was some increase in lesion activity on the MRI scans in patients in CLARITY Extension who received cladribine tablets 3.5 mg/kg in the initial (2-year) phase and then received placebo in the extension phase [16]. This increased lesion activity was mainly in patients who entered the extension phase more than 43 weeks after the end of the randomised phase [16].…”
Section: Clinical Efficacymentioning
confidence: 97%
See 2 more Smart Citations
“…the majority of patients for at least a further 2 years, without further treatment and despite recovery of median total lymphocyte counts to within the normal range. There was some increase in lesion activity on the MRI scans in patients in CLARITY Extension who received cladribine tablets 3.5 mg/kg in the initial (2-year) phase and then received placebo in the extension phase [16]. This increased lesion activity was mainly in patients who entered the extension phase more than 43 weeks after the end of the randomised phase [16].…”
Section: Clinical Efficacymentioning
confidence: 97%
“…The clinical efficacy of cladribine tablets 3.5 mg/kg was evaluated in 1326 patients with RRMS in the CLAdRIbine Tablets treating multiple sclerosis orallY (CLARITY) study, a randomised, placebo-controlled, 96-week clinical trial (Table 1) [10]. Briefly, compared to placebo, cladribine tablets 3.5 mg/kg was associated with 47% reduction in the risk of 6-month EDSS progression in a subgroup with high disease activity at baseline lower relapse rates, a higher proportion of patients with no evidence of disease activity, less progression of disability and a reduction in disease activity as measured by magnetic resonance imaging (MRI) [10][11][12][13][14][15][16]. The reduction in disability progression was greater in patients with higher indices of disease activity at baseline than in those without higher baseline indices of disease activity [13].…”
Section: Clinical Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have demonstrated the efficacy of Cladribine Tablets 3.5 mg/kg over 2 years of follow-up in patients with RMS, including reductions in relapse rates, magnetic resonance imaging (MRI)-based disease activity and progression of disability [46][47][48]. Longer-term efficacy was observed in an extension to a clinical trial in RMS patients that involved a total of 4 years of follow-up [49,50]. Importantly, in this extension study, relapse rates were similar for patients who continued to receive Cladribine Tablets 3.5 mg/kg and those who were re-randomized to placebo [49].…”
Section: Alemtuzumabmentioning
confidence: 99%
“…Cladribine tablets are indicated for adults with highly active RMS as defined by clinical and radiological features [ 30 ]. In clinical trials, cladribine tablets significantly reduced the ARR, probability of disability progression, and brain lesions as compared to placebo over 96 weeks in patients with RRMS [ 11 , 16 , 17 ]. The most common adverse event associated with cladribine tablets is lymphopenia [ 30 ].…”
Section: Overview Of High-efficacy Dmds Used In Rrmsmentioning
confidence: 99%